1977
DOI: 10.1111/j.1471-4159.1977.tb07763.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐hydroxytryptamine Catabolism in the Rat Brain During Ontogenesis

Abstract: Abstract— Although the serotoninergic innervation is immature in the brains of young rats, the 5‐HIAA content is similar to that found in adults. As indicated by the ratio of 5‐HIAA to 5‐HT levels in the brain stem and the forebrain, the catabolism of the indolamine was more rapid during the first 3 postnatal weeks than in adults. This was contirmed by measuring the total formation of [3H]5‐HIAA from [3H]5‐HT newly synthesized from L‐[3H]tryptophan in brain stem slices of young and adult rats. Electrolytic les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 21 publications
9
21
0
Order By: Relevance
“…As previously demon strated for other species [3,6,12] at birth, high 5-HIAA levels have also been observed in the brainstem, most probably due to high 5-HT-specific MAO A activity as recently demonstrated by Bourgoin et al [6] in the newborn rat. The increase of 5-HT level dur ing postnatal life is more marked and more gradual in the forebrain than in the brain stem.…”
Section: -Ht Metabolismsupporting
confidence: 53%
“…As previously demon strated for other species [3,6,12] at birth, high 5-HIAA levels have also been observed in the brainstem, most probably due to high 5-HT-specific MAO A activity as recently demonstrated by Bourgoin et al [6] in the newborn rat. The increase of 5-HT level dur ing postnatal life is more marked and more gradual in the forebrain than in the brain stem.…”
Section: -Ht Metabolismsupporting
confidence: 53%
“…This correlation was later substantiated by a similar study in the rat brain. Bourgoin et al (1977) demonstrated that, in the rat brain, the MAO-A activity was higher during early life than in the adult. On the contrary, the MAO-B activity increased steadily from newborn to the adult brain.…”
Section: Discussionmentioning
confidence: 93%
“…The specific activity of this enzyme in the adult rabbit retina was found to be 4.5 + 0.8 pmol of dopamine degraded/gm of protein/hr. Since two distinct types of MAO, MAO-A and MAO-B, are known to exist in different tissues (Hall et al, 1969;Roth and Gillis, 1975) and follow different developmental patterns (Bourgoin et al, 1977;McCaman and Aprison, 1964), the characteristics of MAO in the rabbit retina were further examined pharmacologically by using specific inhibitors Vol. 1, No.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, since MAO activity is high in the immature brain [3,5,6,16,23], this inhibition of TPH activity could lead to a large-scale depletion of 5-HT in the embryo. Such a deficit, occurring between 8 and 17 days of gestation, at a time when 5-HT may be re quired as a developmental signal, might ac count for our previous observation of altered neuronal genesis in the embryonic brain as a consequence of maternal pCPA treatment [20, 21], The increased activity of embryonic TPH as a result of maternal tryptophan injections Values are means rfcSEM.…”
Section: Resultsmentioning
confidence: 99%